2016
DOI: 10.18052/www.scipress.com/ilns.55.35
|View full text |Cite
|
Sign up to set email alerts
|

Management of Sugar Industrial Wastes through Vermitechnology

Abstract: Abstract. The present paper discusses the role of earthworms in recycling of sugar industrial wastes. The wastes generated from sugar industry are pressmud, bagasse, bagasse fly ash, sugar cane trash, sugar beet mud, sugar beet pulp, molasses etc. These wastes when mixed with other organic substrates become ideal mixtures for growth of earthworms. These wastes if stored in open field's causes contamination in the environment and may cause several diseases in public health. But the governments have been unable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Suthar [1] also observed a significant decrease in TOC due to combined action of earthworms and microorganisms. Similar observations have been reported by Bhat et al [7,10] during vermicomposting of sugar mill waste. Khwairakpam and Bhargava [28] observed that the cattle dung contains various fungal stains and other microbes like bacteria, protozoa, nematodes, fungi, actinomycetes, which play an important role in organic matter decomposition by providing extra-cellular enzymes in vermireactors.…”
Section: Physico Chemical Analysissupporting
confidence: 91%
See 3 more Smart Citations
“…Suthar [1] also observed a significant decrease in TOC due to combined action of earthworms and microorganisms. Similar observations have been reported by Bhat et al [7,10] during vermicomposting of sugar mill waste. Khwairakpam and Bhargava [28] observed that the cattle dung contains various fungal stains and other microbes like bacteria, protozoa, nematodes, fungi, actinomycetes, which play an important role in organic matter decomposition by providing extra-cellular enzymes in vermireactors.…”
Section: Physico Chemical Analysissupporting
confidence: 91%
“…It is clear from the present study that cocoon formation in different waste proportions was directly related to the feedstock quality. The results of cocoon formation are corroborated by the findings of other researchers who have analyzed waste quality dependent cocoon formation patterns in earthworms during the process of vermicomposting [7,20].…”
Section: Earthworm Growth and Reproduction In Waste Mixturessupporting
confidence: 86%
See 2 more Smart Citations
“…Unfortunately, most research has excluded the combination of these reinforcements while the optimisation behaviour of the reinforced composites at room temperature in the water absorption process is not known. The composite industry is one of the most dynamic sectors in the economy in the past few years and an anticipated all-time high is expected in the demand for agro-based composites in the next years [13][14][15]. Consequently, there is a need to have a clearly defined optimisation goal for the reinforcements to be used by combining cocoa pod husk, bagasse and guinea fowl feather with epoxy resin for composite fabrication.…”
Section: Introductionmentioning
confidence: 99%